2019
DOI: 10.1136/rmdopen-2018-000806
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib or adalimumab versus placebo: patient-reported outcomes from OPAL Broaden—a phase III study of active psoriatic arthritis in patients with an inadequate response to conventional synthetic disease-modifying antirheumatic drugs

Abstract: ObjectivesTofacitinib is an oral Janus kinase inhibitor for treatment of psoriatic arthritis (PsA). We evaluated patient-reported outcomes (PROs) in patients with PsA refractory to ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD-IR) and tumour necrosis factor inhibitor-naïve in a 12-month, phase III randomised controlled trial (OPAL Broaden [NCT01877668]).MethodsPatients (N=422) received tofacitinib 5 mg or 10 mg twice daily, adalimumab 40 mg subcutaneously every 2 weeks or placebo adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 41 publications
0
54
0
4
Order By: Relevance
“…Additional pre-specified secondary endpoints of Dactylitis Severity Score (DSS), Medical Outcomes Study 36-Item Short Form Health Survey (SF-36), and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) were in the same direction as the primary endpoints but could not be assessed for significance due to hierarchical statistical testing of secondary endpoints. 11,18 Radiographs of the hands and feet were assessed at baseline and 12 months using the van der Heijde-modified Total Sharp Score (mTSS). At 12 months, 91-98% of patients across all treatment groups met the radiographic criteria for nonprogression of joint damage, defined as a change in mTSS of ≤0.5, ≤0, or ≤0.66 from baseline.…”
Section: Psoriatic Arthritis Clinical Trialsmentioning
confidence: 99%
“…Additional pre-specified secondary endpoints of Dactylitis Severity Score (DSS), Medical Outcomes Study 36-Item Short Form Health Survey (SF-36), and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) were in the same direction as the primary endpoints but could not be assessed for significance due to hierarchical statistical testing of secondary endpoints. 11,18 Radiographs of the hands and feet were assessed at baseline and 12 months using the van der Heijde-modified Total Sharp Score (mTSS). At 12 months, 91-98% of patients across all treatment groups met the radiographic criteria for nonprogression of joint damage, defined as a change in mTSS of ≤0.5, ≤0, or ≤0.66 from baseline.…”
Section: Psoriatic Arthritis Clinical Trialsmentioning
confidence: 99%
“…Tofacitinib is an oral JAK inhibitor for the treatment of RA and PsA, and is under investigation for the treatment of AS. The efficacy of tofacitinib in improving patient-reported outcomes (PROs), including pain, has been demonstrated in PRO components of phase III RCTs in patients with RA22–26 and PsA,27 28 and in a phase II RCT in patients with AS 29…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the baseline characteristics reported from other biological or targeted synthetic disease-modifying antirheumatic drug clinical trials. While different measures of fatigue were used across studies, a trial using the fatigue assessment scale (range 0–10; higher score=greater fatigue) reported baseline scores of 5.8–6.3 across treatment groups,36 trials reporting scores from the FACIT-fatigue (0–52; higher score=less fatigue) reported scores of 24.5–30.8 across treatment groups,37–40 and a trial using a fatigue 0–100 VAS (higher score=greater fatigue) reported scores of 54.7–55.9 across treatment groups 41…”
Section: Discussionmentioning
confidence: 99%